Body image disorder: A study with preadolescents and reflections from the gender perspective - Trujano, Patricia; Nava, Carlos; de Gracia, Manuel; Limón, Gilberto; Lilia Alatriste, Ana; Merino, María Teresa (Anales de Psicología / Annals of Psychology, 2010)
Differences were explored by gender and age through four instruments that assess Body Self-Esteem (BES), General Self-Esteem (LAWSEQ), Eating Attitudes (CHEAT) and Body Image (BIA). The sample consisted of 600 mexicans girls and boys from 9 to 12 years. We found that stereotypes about extreme thinness continue to impact more in girls than in boys, and to the older ones. The gender comparison showed girls with a lower general and body self-esteem than boys; the ideal image (how they want to be) and future image (how they think they will be) of girls was thinner. No significant differences in scores on the Cheat were observed. Regarding to age, body self-esteem was higher in younger ones, but decreased while they were growing. In the real image (how they see themselves) the older ones perceived themselves with thicker figures. The older boys preferred in the future more developed physiques than the young ones. The older girls perceived themselves and thought that others saw them (social image) thicker than they actually were, they also showed lower body self-esteem than the younger ones. The findings were dis-cussed reflexively under a gender perspective.